2022
DOI: 10.3390/su141710689
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Competency, Financial Literacy, and Sustainable Performance—Examining the Mediating Role of Entrepreneurial Resilience among Saudi Entrepreneurs

Abstract: This paper investigated the influence of entrepreneurial competency and financial literacy on sustainable small enterprise performance. We simultaneously investigated the mediating role of entrepreneurial resilience on the association between competence and financial literacy with sustainable business performance. We used a quantitative method for collecting data from 220 small business entrepreneurs in Saudi Arabia using an online questionnaire. The collected data were analysed with the help of PLS-SEM. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
2
33
0
1
Order By: Relevance
“…As suggested by Hurst et al (2008), it may be difficult to summarize an absolute profile of a successful entrepreneur. Although some studies suggest that competencies positively influence business success (Mitchelmore and Rowley, 2013; Agarwal and Lenka, 2017), some other stress on a few specific competencies such as networking ability (Revell-Love and Revell-Love, 2016; Ahmad et al , 2018; Kyrgidou et al , 2021), organizing competency (Zainol and Al Mamun, 2018), social skills (Dimitriadis and Koning, 2021) and financial and entrepreneurial competencies (Brinckmann et al , 2011; Seraj et al , 2022). Most often, direct determinants of growth such as money, market and management interact as female business owners in developing economies make use of their strong nonformal competencies and prior experiences (management) to expand their access to potential market.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Hurst et al (2008), it may be difficult to summarize an absolute profile of a successful entrepreneur. Although some studies suggest that competencies positively influence business success (Mitchelmore and Rowley, 2013; Agarwal and Lenka, 2017), some other stress on a few specific competencies such as networking ability (Revell-Love and Revell-Love, 2016; Ahmad et al , 2018; Kyrgidou et al , 2021), organizing competency (Zainol and Al Mamun, 2018), social skills (Dimitriadis and Koning, 2021) and financial and entrepreneurial competencies (Brinckmann et al , 2011; Seraj et al , 2022). Most often, direct determinants of growth such as money, market and management interact as female business owners in developing economies make use of their strong nonformal competencies and prior experiences (management) to expand their access to potential market.…”
Section: Discussionmentioning
confidence: 99%
“…However, we only explore the different impacts of CFL measured with the two methods on stock market participation behavior. The other finical behaviors, such as retirement planning and investment decision, are also significantly affected by individuals’ CFL (e.g., Liao et al, 2022 ; Yeh and Ling, 2022 ; Seraj et al, 2022a , b ). Therefore, it could be intuitive to check whether the CFL measured by the two methods can produce different marginal effects for other specific financial behaviors in a particular survey data.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be intuitive to check whether the CFL measured by the two methods can produce different marginal effects for other specific financial behaviors in a particular survey data. Additionally, some emerging research fields other than financial behaviors, such as sustainable performance of enterprise affected by the FL of entrepreneur ( Alshebami and Murad, 2022 ; Seraj et al, 2022a , b ), should further considered the impact of the CFL measured with our improved method.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, it is evident that managers and proprietors of manufacturing SMEs possessing robust ECs prioritize long-term performance objectives, emphasizing factors such as environmental sustainability, community well-being and public safety, as highlighted by Al Koliby et al (2022a). The empirical findings indicated that ECs are a notable predictor SP (Seraj et al, 2022). Similarly, Fazal et al (2022) demonstrated that pertinent competencies have a notable and positive impact on the sustainability of businesses.…”
Section: Entrepreneurial Competency and Sustainable Performancementioning
confidence: 97%
“…Similarly, Fazal et al (2022) demonstrated that pertinent competencies have a notable and positive impact on the sustainability of businesses. Consistent with the RBV, which asserts that a company's performance is influenced by intangible processes, empirical evidence indicates that the lack of managerial competencies leads to the failure of SMEs (Seraj et al, 2022). Hence, based on the above, we suggest that: H1.…”
Section: Entrepreneurial Competency and Sustainable Performancementioning
confidence: 99%